Magnesium Sulfate Promoted Efficient and Green Synthesis of Aminoalkyl, Amidoalkyl and Diarylmethane Derivatives - Selva Ganesan*, S.; Asaithampi, G. (Asian Journal of Chemistry, 2014)
Under solvent-free condition, magnesium sulfate promoted the synthesis of substituted aminoalkyl naphthols, amidoalkyl naphthols and diarylmethane derivatives in excellent yield. Robust dehydrating nature and mild Lewis acidity of magnesium sulfate was exploited to carry out all the transformations.